Parler de générosité dans la mission contemporaine - Robert, Marie-Hélène (Warszawskie Studia Teologiczne, 2022)
Is generosity a value, a risk, a counter-value or a question in the contemporary Western context? How is human generosity, aroused and directed by the primary generosity of God, at the heart of the current challenges of the missionary encounter? This reflexion crosses the anthropological, spiritual and biblical dimensions of the notion to answer these questions, beginning by avoiding the pitfalls of generosity. We could see then how to actualize the evangelical call to be "generous as your Father is generous" and explore models of missionary generosity adjusted to that of God and to contemporary expectations so that the Gospel may always be better proclaimed and received.